2023
DOI: 10.3390/agronomy13112823
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Alfalfa Intercropped under Corn in Response to Varying Rates of Prohexadione with or without Fungicide Plus Insecticide

John H. Grabber,
José Luiz C. S. Dias,
Mark J. Renz

Abstract: Establishment of interseeded alfalfa (Medicago sativa L.) under corn (Zea mays L.) silage is enhanced with foliar applications of prohexadione (PHD) followed by fungicide plus insecticide (FI), but the lowest effective rates must be determined. We evaluated stand characteristics of alfalfa interseeded into corn at Arlington, Wisconsin, USA in response to PHD applied at 0 to 0.423 kg a.e. ha−1 followed two weeks later with FI (none vs. 0.147 kg a.i. ha−1 fluxapyroxad-pyraclostrobin plus 0.018 kg a.i. ha−1 lambd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The timing of interseeding after maize planting and the application of PHD had little or no effect on alfalfa stand density in either state (Figure 4). Application of PHD often improves plant survival of interseeded alfalfa in Wisconsin (Grabber, Smith et al., 2021; Osterholz et al., 2018), but other studies carried out under normal to dry growing conditions in the Eastern and Midwestern United States also found that stand density of alfalfa intercropped with maize was in some cases lower than spring‐seeded alfalfa or not responsive to PHD treatment (Berti, Lukaschewsky et al., 2021; Berti, Cecchin et al., 2021; Grabber, Osterholz et al., 2021; Grabber, Dias, & Renz,2023; Patel et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The timing of interseeding after maize planting and the application of PHD had little or no effect on alfalfa stand density in either state (Figure 4). Application of PHD often improves plant survival of interseeded alfalfa in Wisconsin (Grabber, Smith et al., 2021; Osterholz et al., 2018), but other studies carried out under normal to dry growing conditions in the Eastern and Midwestern United States also found that stand density of alfalfa intercropped with maize was in some cases lower than spring‐seeded alfalfa or not responsive to PHD treatment (Berti, Lukaschewsky et al., 2021; Berti, Cecchin et al., 2021; Grabber, Osterholz et al., 2021; Grabber, Dias, & Renz,2023; Patel et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…ha −1 of fungicide (fluxapyroxad and pyraclostrobin) and 0.018 kg a.i. ha −1 of insecticide (lambda‐cyhalothrin) were also applied during establishment to spring‐seeded and interseeded alfalfa in late June or early July to suppress foliar disease and insect pests and to enhance seedling vigor and survival (Grabber, Smith et al., 2021; Grabber, Dias, & Renz, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations